Oncological outcomes of rectal cancer patients with anastomotic leakage: A multicenter case-control study - Peltrini, Roberto; Carannante, Filippo; Costa, Gianluca; Bianco, Gianfranco; Garbarino, Giovanni Maria; Canali, Giulia; Mercantini, Paolo; Bracale, Umberto; Corcione, Francesco; Caricato, Marco; Capolupo, Gabriella Teresa (Frontiers in Surgery, 2022)
Introduction: This study aimed to evaluate the impact of anastomotic leakage (AL) on oncological outcomes after restorative rectal cancer surgery. Methods: Patients who underwent anterior resection for rectal adenocarcinoma between January 2011 and December 2017 were retrospectively reviewed. Data were collected from three colorectal surgery centers. Patients with grade B and C leaks according to the International Study Group of Rectal Cancer classification were identified and compared with the control group. Estimated recurrence and survival rates were compared using the log-rank method and Cox regression analysis. Results: A total of 367 patients were included in the study, with a mean follow-up of 59.21 months. AL occurred in 64 patients (17.4%). Fifteen patients with AL (23.5%) developed local recurrence (LR) compared to 17 (4.8%) in the control group (p<0.001). However, distant recurrence rates were similar (10.9% vs. 9.6%; p=0.914) between the groups. Kaplan-Meier curves showed that patients with AL had a reduced 5-years local recurrence-free survival (96% vs. 78%, log-rank p<0.001). AL (OR 4.576; 95% CI, 2.046–10.237; p<0.001) and node involvement (OR 2.911; 95% CI, 1.240-6.835; p=0.014) were significantly associated with LR in multivariate analysis. AL was significantly associated with DFS only at univariate analysis (HR 1.654; 95% CI: 1.024–2.672; p=0.037), with a difference between 5-year DFS of patients with and without AL (71.6% vs. 86.4%, log-rank p=0.04). Only male gender, pT3-4 stage, and node involvement were identified as independent prognostic factors for reduced DFS in the multivariate Cox regression analysis. Conclusion: In this cohort of patients, AL was associated with a significant risk of LR after rectal cancer surgery.